PENGARUH PENERAPAN CORPORATE GOVERNANCE DAN KEPEMILIKAN ASING TERHADAP PRAKTIK MANAJEMEN LABA DENGAN PROFITABILITAS SEBAGAI VARIABEL PEMODERASI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nicholas Parulian Siregar; Vinola Herawaty (Jurnal Magister Akuntansi Trisakti, 2016)
The objective of the study is to analyze how the board size, independent commissioner, audit committee effectiveness, external auditor quality, institutional share ownership, managerial share ownership as a component of corporate governance and also foreign ownership that moderated with profitability have an effect to earning management practices in manufacturecompanies which listed in Indonesia Stock Exchange.Sampling techniques using a purposive sampling method. This research using 56 manufacture companies which listed in Indonesia Stock Exchange in the period of 2011-2015 as a samples.The result of this research are managerial share ownership has  a negative effect on earnings management practices whereas board size, independent commissioner, audit committee effectiveness,external auditor quality,institutional share ownership and foreign ownership has no effect on earnings management practices. This research is also showed that profitability has no effect on moderating correlation between all independent variables and earnings management practices.